Responsive environments for urbanizing South Africa: Roodepoort as a design case study - Fourie, Willem Jacobus (My University, 2015)
South Africa is in the midst of an unprecedented demographic shift. Our population is rapidly urbanizing, with far-reaching implications for our cities. The majority of the in-migrants to the cities are from educationally and economically disadvantaged rural areas. With people flocking to urban areas, cities find it more and more difficult to meet the basic requirements of their inhabitants in terms of jobs and levels of service, with the result that they place an enormous burden on the newly urbanized inhabitants. This dissertation seeks to explore an alternative to present-day efforts to cope with urbanization. It is recognized that a new mode of city building is needed, capable of guiding rapid urban growth. The study recognizes urbanization as a potential growth resource, with the capacity to reshape urban environments in a meaningful way. People are coming to urban areas to gain access to opportunities, activities and facilities which are generated through urban agglomeration. Agglomeration is seen as the historic genius of urban areas that enables a range, variety and richness of activities and opportunities, which are simply not possible in more dispersed and less specialized settlement forms. Urbanism as a way of life, in the pattern of existence, is suggested as a framework that will give overall direction and vision for a wide range of agents. Urbanity is seen as a structural order necessary to ensure that parts of cities and regions reinforce each other. In this way the potential of urban areas as